Head lice were also affected by COVID-19: A decrease on Pediculosis infestation during lockdown in Buenos Aires - Galassi, Federico Gabriel (2021)
Pediculosis is a worldwide disease affecting school-aged children produced by the presence of the head louse, Pediculus humanus capitis De Geer, an obligate ectoparasite on the human scalp feeding exclusively on blood. Transmission occurs primarily through direct physical head-to-head contact. In March 2020, the World Health Organization (WHO) declared the COVID-19 outbreak as a pandemic. COVID-19 is caused by SARS-CoV-2, a variant of the coronavirus. Therefore, on March 18, 2020, the Argentinean government established mandatory isolation for an indefinite period. This obligatory isolation interrupted regular classes avoiding direct contact between children, thus affecting the dispersal route of individuals and the evolution of head louse populations. In this study, we evaluated through an online survey how confinement affected the prevalence of lice during lockdown compared to the situation prior to confinement. The survey allowed to discriminate the different control strategies, the number of treatments, and the amount of insects recorded by parents. Data of 1118 children obtained from 627 surveys were analyzed. As the main result, it was observed that prevalence of lice decreased significantly from before (69.6%) to during (43.9%) COVID-19 lockdown. Moreover, head lice infestation was more effectively controlled in households with up to 2 children in comparison to households with 3 or more children. This is the first study that analyzed the prevalence of head lice during COVID-19 pandemic. In addition, this work demonstrated the impact of social distance in the population dynamics of head lice and how it could affect the control strategies in the future.